Spatial-temporal baseline study of nutrients and trace elements characterization of a large tropical transition system in West Africa - Celso Paulo; João A. Carreiras; Susanne Tanner; Carmen Van-Dúnem dos Santos; Vanessa F. Fonseca; Bernardo Duarte (Environmental and Sustainability Indicators)
Diogo Cao Bay is a massive transitional system northeast of Angola at the Congo/Zaire River mouth, the second-largest river in the world and the largest river in Africa, making it ideal for urban development. The Bay's physicochemical features, nutrients, and trace element contamination were evaluated to assess the system's anthropogenic pressure. Sediment and water samples were taken via a pressure gradient from Bocolo (BO), Moita Seca (MS), and Pululu (PLO). Water physicochemical characteristics (including nitrogen and phosphorus inorganic forms) varied seasonally, whereas sediments as trace element archives revealed a spatial variation pattern. DIN concentrations were between 8 and 140 times higher, and DIP concentrations were between 1 and 75 times higher than those in previous studies, highlighting the need for a comprehensive monitoring program. Pb and Hg Enrichment Factors (EF) and Sediment Quality Guideline-Quotient (SQG-Q) indicated the presence of anthropogenic contamination with high potential for specific adverse biological effects. Nevertheless, in terms of ecological risk, the majority of the samples were classified as having a low to moderate ecological risk. Within each of the surveyed abiotic compartments (water and sediment), the analyzed elements showed significant correlations with each other, indicating a shared source and accumulation mechanism. The pressure gradient revealed PLO as the most polluted area and BO as a potential reference site for future impact assessment studies. The current results provide key baseline information in a data-poor environment, serving as a stepping stone for future ecological health assessments and conservation efforts of this large transitional system.